"WASTEAPP" Application Based on Android for Household Waste Self-Tracking - Zara Yunizar; Nanda Savira Ersa; Zalfie Ardian; Rusnani Rusnani; Fathan Maulana Helmi (International Journal of Engineering, Science and Information Technology, 2022)
Rapid population growth has both a positive and a negative impact, such as an increase in household waste generation. This also becomes a new chain of problems in other aspects, such as health, flood, air pollution, and environmental pollution. To overcome this problem, an integrated waste management system is needed. Household waste, especially inorganic waste, was valuable. The application was developed to promote a new paradigm; waste is a new source of money. As well as help run a circular economy in the waste recycling industry. The application to be built is "WasteApp", an independent household waste management application that can track and help manage it. This application is built using the Android operating system to make it a user-friendly tool. An application trial was conducted in Geulanggang Baro village, Bireuen district involving the operator, local government, and community. This location was chosen because they already have informal waste management, and it is easier to maximize by information technology intervention. The final result of this research is the â€œWasteAppâ€ application based on android to manage household waste independently. The community, operator, and local government can work waste independently and systematically through this system. This application contains several menus, including the Home menu, login, register, and the main menu, namely the waste sell history and selling waste, as well as educational articles that contain how to manage waste, from sorting waste to the recycling process. Community participation was needed to increase to full implementation of good waste management.